Development of augmented reality-assisted mathematical comics based on Jambi folklore to improve students’ metacognitive skills - Nizlel huda; Husni Sabil; Wardi Syafmen; Novferma (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: This study aims to investigate how the integration of Augmented Reality-assisted mathematical comics based on Jambi folklore can support students’ metacognitive skills in mathematics learning.Method: This study employed a Research and Development approach using the ADDIE model consisting of analysis, design, development, implementation, and evaluation stages. The developed instructional media were validated by a media expert, a mathematics education expert, and an instructional design expert. The implementation stage involved 32 junior high school students divided into an experimental group and a control group. Data were collected through observations, interviews, questionnaires, and metacognitive skills tests, and analyzed using Aiken’s V, descriptive percentage analysis, and an independent sample t-test supported by effect size analysis.Findings: The developed instructional media achieved very high validity, with Aiken’s V values ranging from 0.88 to 0.92, and obtained a practicality score of 86%. Students who learned using the developed media demonstrated better metacognitive skills than those who learned through conventional instruction, with a Cohen’s d effect size of 0.81 indicating a large practical effect. The integration of Augmented Reality visualization, mathematical comic narratives, and contextual cultural content supported students in interpreting mathematical problems, monitoring solution strategies, and reflecting on their answers during learning activities.Significance: This study contributes to metacognitive learning research by demonstrating that Augmented Reality-assisted mathematical comics integrated with local cultural narratives can support reflective and culturally contextualized mathematics learning environments.